Ballard Bunder Gatehouse - Ghosh, Ayan (2023)
The triple-arched Ballard Bunder Gatehouse was built in 1920 to commemorate the repositioning of the Ballard Pier by the Bombay Port Trust. After Independence, the gatehouse became part of the Naval Dockyard but fell into disuse. In 2005, the Western Naval Command restored the building, converting it into a nautical-themed museum.